1999
DOI: 10.1161/01.cir.99.18.2383
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia but Not the C677T Mutation of Methylenetetrahydrofolate Reductase Is an Independent Risk Determinant of Carotid Wall Thickening

Abstract: Mild hyperhomocysteinemia is an independent risk factor for increased carotid artery wall thickness and plaque formation in a general population. Lower levels of dietary folate intake and the C677T mutation in MTHFR are important causes of mild hyperhomocysteinemia and may therefore contribute to vascular disease in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
123
6
5

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(143 citation statements)
references
References 25 publications
9
123
6
5
Order By: Relevance
“…The finding of an interaction effect between smoking and MTHFR(C677T) genotype has not been reported previously. A suboptimal plasma folate status among smokers (Piyathilake et al, 1994;Cafolla et al, 2000;O'Callaghan et al, 2002) might explain the observed interaction, as plasma folate has been shown to interact with MTHFR(C677T) genotype (Jacques et al, 1996b;Brattstrom et al, 1998;Girelli et al, 1998;McQuillan et al, 1999;Dekou et al, 2001;Saw et al, 2001). The involvement of folate is further supported by another study in which smoking was reported to interact with the dietary intake of folate (De Bree et al, 2001b).…”
Section: Discussionmentioning
confidence: 99%
“…The finding of an interaction effect between smoking and MTHFR(C677T) genotype has not been reported previously. A suboptimal plasma folate status among smokers (Piyathilake et al, 1994;Cafolla et al, 2000;O'Callaghan et al, 2002) might explain the observed interaction, as plasma folate has been shown to interact with MTHFR(C677T) genotype (Jacques et al, 1996b;Brattstrom et al, 1998;Girelli et al, 1998;McQuillan et al, 1999;Dekou et al, 2001;Saw et al, 2001). The involvement of folate is further supported by another study in which smoking was reported to interact with the dietary intake of folate (De Bree et al, 2001b).…”
Section: Discussionmentioning
confidence: 99%
“…Subjects were selected from two populations: the Carotid Ultrasound Disease Assessment Study (CUDAS) (19) and the Busselton Population Health Survey (20). These two populations were predominantly Caucasian and were collected from the same region of Western Australia.…”
Section: Methodsmentioning
confidence: 99%
“…26,27 In brief, this was a random electoral roll sample of 1111 predominantly Caucasian subjects aged 27-77, mean 53 years, from Perth, Western Australia, who were assessed for cardiovascular risk factors and had carotid B-mode ultrasound performed. The numbers of subjects were equally distributed between sexes and across each age decile.…”
Section: Study Populationmentioning
confidence: 99%